Restorative Justice as a Legal Policy on Criminal Punishment: An Integrative Study of Legal Certainty and Substantive Justice - Deny Deny; Wolter Junaedi Nurhamidin; Ana Maria Gadi Djou; Yulianis Safrinadiya Rahman; Iwan Rasiwan (Journal of Law, Politic and Humanities, 2026)
The concept of restorative justice has emerged as a contemporary paradigm in modern criminal justice systems, shifting the focus away from mere retribution toward the restoration of social relationships and the reparation of harm suffered by victims. This transformation reflects a broader change in the direction of criminal law policy toward a more humane and justice-oriented approach. This study aims to examine restorative justice within the framework of criminal law policy, with particular emphasis on the integration of legal certainty and substantive justice. The research employs a normative legal method, utilizing conceptual, statutory, and comparative approaches to achieve a comprehensive analysis. The findings indicate that restorative justice holds significant potential in reconciling the tension between formal legal procedures and the evolving sense of justice within society. However, its implementation continues to face several challenges, including inconsistencies in law enforcement practices, limited technical regulations, and the need for a paradigm shift among legal practitioners. Therefore, strengthening policy frameworks and establishing clear operational guidelines are essential to ensure the effective and consistent application of restorative justice.